320 STEROID-FREE IMMUNOSUPPRESSION FOR RENAL TRANSPLANTATION: A SINGLE-CENTER EXPERIENCE. Issue 1 (1st January 2007) - Lau, K.; Haddad, M.; Perez, R.; Butani, L.
Abstract : Purpose: To determine the outcomes of immunosuppression with early withdrawal of steroid in pediatric renal transplantations (tx) patients at a single Northern California center. Introduction: Although steroid has been a main agent used for post tx immunosuppression, its use is associated with numerous side effects. Protocols using minimal steroid have been reported with success. We examined the outcomes of our children who were managed by a protocol with very early discontinuation of steroid after renal tx. Methods: We retrospectively studied the renal tx recipients at the children hospital at University of California, Davis Medical Center from January 2004 to December 2005. All patients were below age 18 at the time of tx. Protocol included three tapering daily doses of steroid, together with five doses of thymoglobulin and then maintained on tacrolimus and mycophenolate mofetil after tx. Data collected include age, sex, ethnicity, and preemptive tx or mode of renal replacement prior to tx. Medicines required pre- and post-tx, including antihypertensive, statins, erythropoietin, and anti-diabetics, were also recorded. Laboratory values included the serum creatinine, hemoglobin, white cell counts, blood glucose, and cholesterol were also recorded for analysis. Results: Eight patients with equal numbers of male and females were studied. There were equal numbers of Caucasians, African Americans, Hispanics, and Asian patients; 37.5% received preemptive tx, 25% received peritoneal, and 37.5% received hemodialysis before tx. The mean age at tx was 10.8 years, with an average length of follow up of 1.4 years. At 1 year post-tx, 50%, 17%, and 67% of patients still required antihypertensive, erythropoietin, and statins, respectively. Compared with pretransplant levels, mean serum creatinine improved from 9.3 to 1.3 mg/dL ( p < .05); hemoglobin changed from 12.3 to 12.4 g/dL ( p = .9); white blood cell counts changed from 8.5 to 5.6 × 10 3 /L ( p < .05); blood glucose levels remained the same at 86 mg/dL ( p = .98); and cholesterol levels improved from 180 to 158 mg/dL ( p = .4); 12.5% of patients switched from tacrolimus to sirolimus due to calcineurin nephropathy. No patient became diabetic or required hypoglycemic agents. Surveillance biopsies showed no acute rejection on all the patients. Conclusions: Steroid-free immuosuppression is safe in children after renal tx. A larger number of patients and longer follow-up are required to further confirm the effectiveness and safety of steroid-free immunosuppression.